2004
DOI: 10.1021/om0495877
|View full text |Cite
|
Sign up to set email alerts
|

Allylic Substitution Mediated by Water and Palladium:  Unusual Role of a Palladium(II) Catalyst and ESI-MS Analysis

Abstract: Allylic substitution of PhCH(OAc)CHdCHPh by CH 2 (COMe) 2 in a basic MeOH/H 2 O mixture could be achieved in the absence of a palladium catalyst and lead to a mixture of PhCH(CH(COMe) 2 )CHdCHPh and PhCH(OMe)CHdCHPh in 40% and 55% yields, respectively. The process is induced by water, and nucleophilic attack addition occurred on a stabilized carbocation as the intermediate. Addition of a catalytic amount of PdCl 2 (CH 3 CN) 2 did not accelerate the reaction but improved the selectivity, and PhCH(CH(COMe) 2 )CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…A mechanism for this transformation was proposed based on the intercepted species (Scheme 10) [65]. The role of Pd II in improving the selectivity of carbon-carbon bond formation in the allylic substitution of 1-acetoxy-1,3-diphenylpropene by acetylacetone in an aqueous system was investigated by Muzart and Roglans (Scheme 11) [15]. Scheme 11.…”
Section: Adventitiously-charged Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanism for this transformation was proposed based on the intercepted species (Scheme 10) [65]. The role of Pd II in improving the selectivity of carbon-carbon bond formation in the allylic substitution of 1-acetoxy-1,3-diphenylpropene by acetylacetone in an aqueous system was investigated by Muzart and Roglans (Scheme 11) [15]. Scheme 11.…”
Section: Adventitiously-charged Systemsmentioning
confidence: 99%
“…Since then, the primary use of ESI-MS in the area of solution-phase organometallic chemistry has been in the identification of short-lived, low concentration intermediates from catalytic mixtures. Toward this end, ESI-MS has been used to study catalytic oxidations [5][6][7][8], hydrogenations [9][10][11], hydrosilylations [12] and carbon-carbon bond-forming [13][14][15] reactions with the most attention given to palladium-catalyzed carbon-carbon bond-forming reactions [14,[16][17][18][19][20][21]. A number of book chapters have been written on the subject of ESI-MS analysis of organometallic reaction intermediates [22][23][24] and this review aims to highlight more recent advances and new directions in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In an ongoing study using water as a solvent in palladium chemistry, Muzart et al [49,50] described the substitution of allylic acetates 51 with different nucleophiles such as acetylacetone (52) and sodium para-toluenesulfinate (54) in aqueous media using a palladium complex and the hydrophilic ligand [(HOCH 2 CH 2 NH-COCH 2 ) 2 NCH 2 ] 2 (56). Scheme 7.27 shows the specific reactions studied by ESI-MS in order to further investigate mechanistic aspects of these reactions.…”
Section: Esi-ms Studies In Palladium-catalyzed Allylic Substitution Rmentioning
confidence: 99%
“…Muzart et al [54] applied the analytical tool to study mechanistically the hydroxyalkoxylation of o-allylphenol 76 catalyzed by a mixture of Pd(OCOCF 3 ) 2 and the watersoluble ligand 56 (also used in the palladium-catalyzed substitution of allylic acetates in aqueous media [49,50]) with H 2 O 2 in H 2 O/MeOH to afford 2-(1,2-dihydroxypropyl)phenol derivatives 77 and 78 (Scheme 7.32). It was suggested that the reaction went through a cascade process in which, in a first step, isomerization of the double bond took place followed by epoxidaton of the olefin and the opening of the resulting oxirane (Scheme 7.32).…”
Section: Esi-ms Studies In Palladium-catalyzed Oxidation Of 2-allylphmentioning
confidence: 99%
“…Electrospray ionization mass spectrometry (ESI-MS) is a powerful tool in the identification of organometallic reaction intermediates and has been applied to the detection of intermediates in palladium-catalyzed cross coupling reactions. [15][16][17][18][19][20][21][22] However, these studies are essentially focused on the identification of palladium intermediates. Thus, we applied the ESI-MS in the negative mode to detect the boron species in the coupling reaction with (E)-bromostilbene.…”
Section: Resultsmentioning
confidence: 99%